THE EFFECT OF USING GUIDED NOTE TAKING TECHNIQUE ON READING COMPREHENSION TO THE STUDENTS’ ABILITY OF GRADE ELEVEN SMA NEGERI 4 PEMATANG SIANTAR - Megawati Rajagukguk; Melda Veby Ristella Munthe; Siska Anggita Situmeang (Jurnal Scientia, 2023)
The objective this research to find out using guided note-taking technique has significantly effect for students’ in reading comprehension on grade eleven of SMA Negeri 4 Pematang Siantar. The research design is quantative data with quasi experimental. This research have 2 sample for give test main idea and relevant idea such as XI PMIA 2 as experimental group have 36 students and XI PIS 1 as control group have 36 students. The test use is multiple choice with 25 questions contain narrative text. This research means to find whether using Guided Note taking bring students increase reading comprehension and researcher find out results both of Pre-Test and Post-test experimental and control group. Based data, result mean pre-test and post-test experimental group are 64,77 and 81,77. But, in control group result mean pre-test and post-test are 57,33 and 64, it’s mean there is increase use this technique. So on the result mean variable and standar deviation of pre-test and post-test experimental and control class, sum of total pre-test and post-test in the experimental are 17,58 and 511,9 and sum of total mean variable and standar deviation in control group are 10,33 and 177,2 with result t-test 8,63 is higher than t-table at 5% of level significance ( 166,7), it means Ha is accepted and Ho is rejected. The conclusion all of this research is there significant in reading comprehension use Guided Note Taking of grade eleven SMA N 4 Pematang Siantar.